Precise Manipulation of Multilength Scale Morphology and Its Influence on Eco‐Friendly Printed All‐Polymer Solar Cells. (17th July 2017) - Ye, Long; Xiong, Yuan; Li, Sunsun; Ghasemi, Masoud; Balar, Nrup; Turner, Johnathan; Gadisa, Abay; Hou, Jianhui; O'Connor, Brendan T.; Ade, Harald
Abstract : Significant efforts have lead to demonstrations of nonfullerene solar cells (NFSCs) with record power conversion efficiency up to ≈13% for polymer:small molecule blends and ≈9% for all‐polymer blends. However, the control of morphology in NFSCs based on polymer blends is very challenging and a key obstacle to pushing this technology to eventual commercialization. The relations between phases at various length scales and photovoltaic parameters of all‐polymer bulk‐heterojunctions remain poorly understood and seldom explored. Here, precise control over a multilength scale morphology and photovoltaic performance are demonstrated by simply altering the concentration of a green solvent additive used in blade‐coated films. Resonant soft X‐ray scattering is used to elucidate the multiphasic morphology of these printed all‐polymeric films and complements with the use of grazing incidence wide‐angle X‐ray scattering and in situ spectroscopic ellipsometry characterizations to correlate the morphology parameters at different length scales to the device performance metrics. Benefiting from the highest relative volume fraction of small domains, additive‐free solar cells show the best device performance, strengthening the advantage of single benign solvent approach. This study also highlights the importance of high volume fraction of smallest domains in printed NFSCs and organic solar cells in general. Abstract : Precise control over the multilength scale morphology of printed all‐polymer photovoltaic films by altering the concentration of a green additive is demonstrated by means of resonant soft X‐ray scattering, in situ spectroscopic ellipsometry, and complementary methods. Additive‐free nonfullerene devices show the best device performance due to the highest relative volume fraction of small domains and minimized length scale of large domains.